Discrimination of Acori Tatarinowii Rhizoma and Acori Calami Rhizoma based on quantitative gas chromatographic fingerprints and chemometric methods. Issue 23 (27th October 2015) - Zhang, Xiaojuan; Yi, Lunzhao; Deng, Baichuan; Chen, Lian; Shi, Shuting; Zhuang, Yongliang; Zhang, Yi
Abstract : This study was conducted to investigate the chemical differences between Acori Tatarinowii Rhizoma and Acori Calami Rhizoma using gas chromatography with mass spectrometry and chemometric methods. Quantitative fingerprints were established. A total of 90 volatile compounds were identified and quantified using heuristic evolving latent projection and retention index. An efficient model based on partial least squares‐discriminant analysis coupled with variable iterative space shrinkage approach was developed to distinguish Acori Tatarinowii Rhizoma from Acori Calami Rhizoma . The correct rate was 95.83%, and the area under the receiver operating characteristic curve was 100%. Finally, three volatiles, namely, camphor, longicyclene, and δ‐cadinene, were selected as key discrimination factors between Acori Tatarinowii Rhizoma and Acori Calami Rhizoma . The proposed protocol can serve as a valid strategy for quality control and screening of potential bioactive components of herbal medicines.